LEGAL FRAMEWORK FOR ERADICATING FRAUDULENT INVESTMENT AND LEGAL PROTECTION FOR INVESTORS - Muh Bambang Taufik (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2024)
ABSTRACT The quantity of legislation that is too much and the quality of legislation that is not good results in the absence of legal certainty for investors. This research is conducted with the aim of knowing the legal framework for eradicating fraudulent investment, as well as to know the form of legal protection for victims of fraudulent investment crimes. The method used in this research is normative juridical research method, namely collecting legal materials through literature review by examining legal documents related to the issues raised. The research found that the legal framework for eradicating fraudulent investment and legal protection efforts for investors in Indonesia still have several problems, such as too many investment laws and regulations that result in obesity and hyperregulation. Fraudulent investment is a business activity in the form of collecting funds from the public that is contrary to the provisions of banking law, because it violates Law No. 7 of 1992 jo Law No. 10 of 1998 concerning Banking. Therefore, the government needs to evaluate and simplify investment regulations to make them easier for investors to understand and implement. In addition, the government also needs to improve supervision of financial and investment institutions in Indonesia to prevent fraudulent investments. Keywords: Fraudulent Investment; Investor; Legal Protection.